2017
DOI: 10.1089/neu.2016.4657
|View full text |Cite
|
Sign up to set email alerts
|

The Estimated Verbal GCS Subscore in Intubated Traumatic Brain Injury Patients: Is it Really Better?

Abstract: The Glasgow Coma Scale (GCS) has limited utility in intubated patients due to the inability to assign verbal subscores. The verbal subscore can be derived from the eye and motor subscores using a mathematical model, but the advantage of this method and its use in outcome prognostication in traumatic brain injury (TBI) patients remains unknown. We compared the validated "Core+CT"-IMPACT-model performance in 251 intubated TBI patients prospectively enrolled in the longitudinal OPTIMISM study between November 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…There are few studies, noted to different calibration for these predictive models. [152930] These discrepancies and different sensitivity and specificity values in some studies[528] can be elucidate by the fact that a predictive model based on validation and testing set from one population when transferred to another population without modification will often lose its accuracy. [15] By recalibrating these models frequently, we may be overcome these problems with taking into account the changes in settings, quality of care and improved survival.…”
Section: Discussionmentioning
confidence: 99%
“…There are few studies, noted to different calibration for these predictive models. [152930] These discrepancies and different sensitivity and specificity values in some studies[528] can be elucidate by the fact that a predictive model based on validation and testing set from one population when transferred to another population without modification will often lose its accuracy. [15] By recalibrating these models frequently, we may be overcome these problems with taking into account the changes in settings, quality of care and improved survival.…”
Section: Discussionmentioning
confidence: 99%
“…One of the greatest obstacles in the assessment of verbal response is endotracheal intubation. [22][23][24][25][26] New methods include assigning the lowest possible score to untestable components and pseudoscoring missing values on the basis of testable features. 24 Our study found a substantial (not near-perfect) level of agreement among observers for patients' verbal responses, possibly because of the challenges associated with assigning scores for intubated patients.…”
Section: Verbal Responsementioning
confidence: 99%
“…The resulting unreliable GCS scores may affect prognostication, treatment, and decision-making by health care providers. 25 In our study, we advised observers to evaluate nonsedated, intubated patients' verbal responses by having patients write or point to letters if they were able to obey commands. Health care providers need precise information to assign accurate values to the untestable verbal components for patients receiving mechanical ventilation.…”
Section: Verbal Responsementioning
confidence: 99%
“…In the few studies that undertook a sensitivity analysis, imputation was compared with exclusion of missing values. [26][27][28][29][30] A sensitivity analysis can specifically test any bias that the researcher is concerned about. For example, if one suspects that patients with good recovery are less inclined to return for followup, one could specifically impute more favorable outcomes for the lost patients to assess whether the conclusions still hold.…”
mentioning
confidence: 99%